Analisis Hukum Terhadap Penipuan Tiket Konser dan Penegakan Hukum Atas Penipuan Transaksi Digital - Pane, Elisabet Nauli; Ramadhani, Sinta; Choirunnisa, Audi Nayla; Cahyaningrum, Reyva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
in this fast-paced digital era, online concert ticket purchases have become a common practice among music enthusiasts. However, this convenience is often accompanied by a surge in fraud cases, such as concert ticket fraud and other digital transaction frauds. These crimes target individuals who are less vigilant or lack knowledge of digital security, and often occur on e-commerce platforms or social media. This research analyzes the law enforcement against digital transaction fraud, especially concert ticket fraud, and highlights the importance of law enforcement by authorized parties to ensure citizen compliance. Based on Article 378 of the Criminal Code (KUHP), fraud is punishable by a maximum imprisonment of four years. Law enforcement, according to Soerjono Soekanto, focuses on harmonizing values manifested in norms to create, maintain, and preserve peace in social life